Enhancing CO2 electrolysis through synergistic control of non-stoichiometry and doping to tune cathode surface structures - Lingting Ye (Nature Portfolio, 2017)
Carbon dioxide electrolysers are promising for chemical storage of renewable electricity; however, achieving effective adsorption/activation of CO2 is still an issue. Here the authors make a perovskite titanate cathode where non-stoichiometry and chemical doping are used to tune the surface structures, facilitating CO2reduction.